Синтез багатовимірної системи керування для прецизійного комплексу штучного мікроклімату - Pankratova, Nataliya D.; Bidyuk, Petro I.; Golinko, Igor M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2020)
The article considers the synthesis procedure for multidimensional digital controller embedded into industrial artificial microclimate systems. The methodology is proposed for constructing the complex dynamic mathematical model for industrial air conditioners represented in the state space of a combined multidimensional controlled system. An analysis of possible control system optimization criteria is performed. Also, the synthesis procedure for an optimal multidimensional digital linear quadratic controller is given. The feedback matrix is synthesized that determines the control vector optimal trajectory using controlled system states by minimizing the quadratic quality criterion. The proposed multidimensional linear digital controller has a feature of logical selection for elements of industrial equipment for performing the optimal control of a microclimate conditioner. The proposed approach allows for reconfiguring the synthesis procedure for the industrial conditioners automatic control system on the basis of delimiting the mutual influence of control parameters.